Concise Commentary on The Bharatiya Nyaya Sanhita 2023 - Anjan Prakash, Anuj Prakash (Lucknow LexisNexis Publishers, 2024)
School of Law, Governance and Public Policy
MIR No: 194
Order Date: 2024-09-26
Order No: CU/OPEX/LIBRARY/36/2024-25
Received Date: 2024-10-24
Keywords: Law, Criminal Law